Literasi Informasi Generasi X dalam Menghadapi Disinformation Menjelang Pemilu Presiden 2024 - Naufal Adri Juliano; Yuli Rohmiyati (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2026)
The 2024 presidential election has become a platform for spreading various pieces of election-related disinformation by irresponsible individuals in order to sway public opinion and gain as many votes as possible for each presidential candidate. In this case, information literacy is an important skill for the community, especially Generation X, which is one of the groups that is vulnerable to being influenced by disinformation about the election. The purpose of this study is to determine the information literacy of Generation X in Klaseman Hamlet, Salatiga City, in dealing with disinformation ahead of the 2024 presidential election. The research method used a qualitative research method with a phenomenological approach to understand the experiences and abilities of Generation X in Klaseman Hamlet in recognizing, assessing, and responding to information during the 2024 presidential election. The results showed that Generation X in Klaseman Hamlet still often had difficulty distinguishing between factual or false information, especially information sourced from social media. However, some of Generation X in Klaseman Hamlet showed awareness of the importance of verifying the information they obtained.